Olympic combat sports and mental health in children and adolescents with disability: a systematic review of controlled trials - Lee, Youngjun; Guidotti, Flavia; Capranica, Laura; Pesce, Caterina; Benzing, Valentin; Hauck, Janet; Ciaccioni, Simone (Frontiers in Psychology, 2025)
IntroductionChildren and adolescents with disabilities face increased mental health challenges and lack of access to exercise. Olympic combat sports (OCS) such as judo, taekwondo, and others might encourage social engagement, self-control, and resilience. However, not much is known about their mental health impact on this population.MethodsFollowing PRISMA-P protocols (PROSPERO registration: CRD42023452489), we searched seven databases for randomized controlled trials or non-randomized trials that evaluated the impact of OCS on mental health in children and adolescents (5–18 years) with developmental or physical disabilities. The key findings fell into 11 domains across mental illness attitudes, social skills, and mental health literacy. We also extracted individual (e.g., age) and social (e.g., family participation) moderating factors. Rob 2.0 (randomized trials) and ROBINS-I (non-randomized trials) were used to measure the risk of bias.ResultsTwelve studies (seven randomized, five controlled trials) conducted during 1975–2022, encompassing 436 participants (11.4 ± 2.8 years), were included. There were significant improvements (p < 0.05) in stereotypy, communication, social–emotional functioning, and executive function, with occasional improvements in self-esteem and stress management. Several experiments reported rapid hormonal changes (e.g., cortisol) immediately after OCS, particularly among adolescents. Family involvement and age emerged as potential moderators, with older children and adolescents with engaged carers likely to benefit even more.DiscussionsDespite different study protocols, outcomes, and risk-of-bias thresholds, OCS interventions overwhelmingly seem to enhance mental health in children and adolescents with disabilities. More substantial, longer-term trials would be required to validate these findings, explain the processes, and evaluate safety. Programs based on OCS that address disabilities could provide broad pathways to physical activity and psychological development as part of a whole-person developmental model.ConclusionThis review indicates that OCS interventions have the potential to improve mental health outcomes for children and adolescents with disabilities by increasing social skills and executive functioning while better regulating stress. The diversity of samples and inadequate study designs necessitate additional high-quality research.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023452489, CRD42023452489.